2013
DOI: 10.1002/mc.22021
|View full text |Cite
|
Sign up to set email alerts
|

CD44/Cellular prion protein interact in multidrug resistant breast cancer cells and correlate with responses to neoadjuvant chemotherapy in breast cancer patients

Abstract: Multidrug resistance (MDR) is one of the most important factors leading to chemotherapeutic failure in patients with breast cancer. The invasive/metastatic ability of MDR cells is strengthened compared with their parental cells. However, the mechanisms underlying MDR have not been fully elucidated. We found that CD44 and the cellular prion protein (PrPc) were both overexpressed in MDR cells (MCF7/Adr and H69AR). Subsequently, we chose the human breast cancer cell line MCF7/Adr, which is resistant to adriamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 35 publications
2
51
1
3
Order By: Relevance
“…It has been suggested that gain of PrP c function may contribute to cancer growth and metastasis in patients with PrP c -associated cancer (25,26). Previous studies on PrP c in cancer are generally consistent with the notion that PrP c expression increases resistance to cytotoxicity (27)(28)(29)(30)(31).…”
Section: Effect Of Fucoidan On Ht29 Colon Cancer Cell Apoptosis Htmentioning
confidence: 59%
“…It has been suggested that gain of PrP c function may contribute to cancer growth and metastasis in patients with PrP c -associated cancer (25,26). Previous studies on PrP c in cancer are generally consistent with the notion that PrP c expression increases resistance to cytotoxicity (27)(28)(29)(30)(31).…”
Section: Effect Of Fucoidan On Ht29 Colon Cancer Cell Apoptosis Htmentioning
confidence: 59%
“…Moreover, more recently it was suggested that PrP C might also promote human tumor development and diffusion, and the induction of drug resistance [22, 36]. PrP C overexpression was observed in gastric cancer lesions as compared to non-tumor tissues representing a predictive marker of poor prognosis [66], while PrP C down-regulation reduced tumor cell proliferation [67] or caused cell death via the activation of the autophagic pathway [68]. However, most of these studies have been performed in continuous cell lines evaluating the effects of PrP C on the biological behavior of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…33 Moreover, PrP c interacts with CD44 and both proteins enhance the ability of migration and invasion of breast cancer cells. 36 Surprisingly, in this latter study, a predominant nuclear localization of PrP c in the breast tumor samples was observed, which, as emphasized by the authors, needed further investigations. In that context, it is interesting to note that CD44 is a target gene of Wnt effectors, the b-catenin/TCF complex, 37 that we demonstrated activated by nuclear PrP c .…”
Section: Prp C Interaction With Junctional and Nuclear Partners: A Romentioning
confidence: 56%